Answer:
(a). The average speed is 51.83 m/s.
(b). The average velocity over one revolution is zero.
Explanation:
Given that,
Angular velocity = 110 rev/m
Radius = 4.50 m
(a). We need to calculate the average speed
Using formula of average speed
![v=r\omega](https://tex.z-dn.net/?f=v%3Dr%5Comega)
![v = 4.50\times110\times\dfrac{2\pi}{60}](https://tex.z-dn.net/?f=v%20%3D%204.50%5Ctimes110%5Ctimes%5Cdfrac%7B2%5Cpi%7D%7B60%7D)
![v=51.83\ m/s](https://tex.z-dn.net/?f=v%3D51.83%5C%20m%2Fs)
(b). The average velocity over one revolution is zero because the net displacement is zero in one revolution.
Hence, (a). The average speed is 51.83 m/s.
(b). The average velocity over one revolution is zero.
Answer:
0.06 N
1.08 m/s
Explanation:
m = mass of the fan cart = 0.250 kg
a = acceleration of the fan cart = 24 cm/s² = 0.24 m/s²
F = Net force on the cart
Net force on the cart is given as
F = ma
F = (0.250) (0.24)
F = 0.06 N
v₀ = initial velocity of the cart = 0 m/s
v = final velocity of the cart
t = time interval = 4.5 s
Using the equation
v = v₀ + a t
v = 0 + (0.24) (4.5)
v = 1.08 m/s
Answer:
(a) - 42700 m/s
(b) - 6.8 x 10^-4 m/s^2
Explanation:
initial velocity of star, u = 20.7 km/s
Final velocity of star, v = - 22 km/s
time, t = 1.99 years
Convert velocities into m/s and time into second
So, u = 20700 m / s
v = - 22000 m/s
t = 1.99 x 365.25 x 24 x 3600 = 62799624 second
(a) Change in planet's velocity = final velocity - initial velocity
= - 22000 - 20700 = - 42700 m/s
(b) Accelerate is defined as the rate of change of velocity.
Acceleration = change in velocity / time
= ( - 42700 ) / (62799624) = - 6.8 x 10^-4 m/s^2
-GMm/2r is the total energy of the mass m if it is in a circular orbit about mass M.
Given
A particle of mass m moving under the influence of a fixed mass's M, gravitational potential energy of formula -GMm/r, where r is the separation between the masses and G is the gravitational constant of the universe.
As the Gravity Potential energy of particle = -GMm/r
Total energy of particle = Kinetic energy + Potential Energy
As we know that
Kinetic energy = 1/2mv²
Also, v is equals to square root of GM/r
v = √GM/r
Put the value of v in the formula of kinetic energy
We get,
Kinetic Energy = GMm/2r
Total Energy = GMm/2r + (-GMm/r)
= GMm/2r - GMm/r
= -GMm/2r
Hence, -GMm/2r is the total energy of the mass m if it is in a circular orbit about mass M.
Learn more about Gravitational Potential Energy here brainly.com/question/15896499
#SPJ4